Self-Reported Visual Quality of Life After Combat Ocular Trauma. (1st March 2017) - McLaughlin, Andrew; Colyer, Marcus H.; Ryan, Denise S.; Sia, Rose K.; Weichel, Eric D.; Spiegelman, Andrew; Eaddy, S. G.; Mazzoli, Robert A.; Bower, Kraig S.
ABSTRACT: Objectives: To describe the visual outlook and quality of life of service members after combat ocular trauma. Methods: In a single-center, prospective observational study of service members sustaining ocular trauma, participants underwent a series of ocular examinations and noninvasive tests, including the National Eye Institute Visual Functioning Questionnaire (VFQ-25). Results: Of the 165 enrolled participants, 137 completed the VFQ-25. The mean VFQ-25 composite score was 74.4 ± 20.7 (range: 1.4–100). Among 118 participants with visual acuity assessment, 92% had best corrected visual acuity (BCVA) of 20/20 or better in at least one eye. Among participants with severe vision loss (BCVA ≤20/200), there was no statistically significant difference in self-reported general health compared to those without severe vision loss ( p = 0.17). However, there was a significantly lower visual quality of life reported in the composite score and all of the 11 subscales of the VFQ-25. Conclusions: While this study provides evidence that combat ocular trauma is associated with a lower visual quality of life, limitations include the relatively small sample size and the limited documentation of the use of eye protection at time of injury among participants.